Legenda Situ Patenggang Sebagai Objek Daya Tarik Wisata Alam Di Bandung Selatan - Yunisa Maharani (Lembaga Pengembangan Kinerja Dosen, 2023)
South Bandung is an area in West Java which is famous for the beauty of its natural tourism which is so beautiful and extraordinarily amazing, where in the South Bandung area there are many natural tourist attractions that are an attraction for domestic and foreign tourists. One of them is Situ Patenggang which is a beautiful lake located in Rancabali, Ciwidey, Bandung Regency, West Java Province. Behind the beautiful lake there is a legendary love story in Situ Patenggang which is a natural tourist attraction in South Bandung and an iconic lake in Ciwidey, Rancabali, Bandung Regency, West Java. The theory used is the theory of natural tourist attraction objects. The research method used is the interview method, aiming to dig deeper into how this legend can be preserved as a natural tourist attraction object from Situ Patenggang. This interview method was conducted through informants consisting of managers, community leaders, and local communities. The results of the research based on the results of direct analysis show that Situ Patenggang is a lake full of legends so that it attracts many domestic and foreign tourists who make this lake the main object of attraction because of the legendary myths in South Bandung.